To swim or to jump? Passage behaviour of a potamodromous cyprinid over an experimental broad‐crested weir. (17th November 2017) - Amaral, S.D.; Branco, P.; Katopodis, C.; Ferreira, M.T.; Pinheiro, A.N.; Santos, J.M.
Abstract: Physical stressors, such as man‐made obstacles, are considered one of the main causes that negatively affect freshwater fish. Even small weirs may impact fish populations, including potamodromous cyprinids, by partially or totally blocking upstream migratory movements. Some studies have addressed the effect of key hydraulic parameters on upstream movements past small weirs, but little is known on how these parameters interact to induce swimming or jumping behaviour in negotiating such obstacles. This study aims to evaluate the passage behaviour (swimming vs. jumping) of Iberian barbel ( Lucio barbus bocagei ), a potamodromous species, over an experimental small broad‐crested weir, considering the effect of different plunge pool depths (D), waterfall heights (H), and weir discharges (Q). Results revealed that passage behaviour was highly dependent on combinations of plunge pool depths and waterfall heights. Barbel navigated most configurations by swimming (overall outcomes: 81.5% swimming vs. 18.5% jumping), except the ones with the higher waterfall heights (25 cm) tested. Therefore, higher waterfalls proved to be preponderant in the switching of passage behaviour from swimming to jumping. Regarding the discharge over the 1‐m‐wide weir (overall outcomes: 85% swimming vs. 15% jumping), contrary to what was expected, there was no evidence that passage behaviour was discharge‐related, for the range of discharges tested (25–100 L/s). These results are useful to identify potential migration obstacles and should be taken into consideration in river restoration projects and when designing fishways for potamodromous cyprinids.